Land use and farming systems at the periphery of the Crocker Range National Park Sabah, Malaysia - Dimbab, Ngidang; Gabriel Tonga, Noweg; Abdul Rashid, Abdullah (Researchgate, 2003)
Shifting cultivation which usually employs slash-and-burn farming practice and commonly interwoven with cultural attributes of the Murut and Dusun communities, is now a dying culture. This paper argues that the transformation of this age-old farming system is attributed to both external and internal factors.